The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1002/pen.23916
|View full text |Cite
|
Sign up to set email alerts
|

Processing and characterization of microwave and ultrasonically treated waste-EPDM/LDPE polymer composites

Abstract: Composites have been prepared from devulcanized waste ethylene propylene diene monomer (W‐EPDM) rubber by blending with low‐density polyethylene (LDPE) in a twin‐screw extruder. W‐EPDM was treated separately by optimized microwave and ultrasonic radiation. Effect of compatibilizer such as ethylene octane elastomeric copolymer (POE) on the enhancement of mechanical properties of composites was also studied in addition to the radiation treatment. The enhancement of tensile strength (TS) and elongation at break o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 23 publications
0
20
0
Order By: Relevance
“…The microwave devulcanization, used in this study, has proved to be an efficient technique. This method enables to apply large amounts of energy rapidly and uniformly to the rubber, without using chemical reagents during the process [17,18], which makes it an eco-friendly process [19]. The energy used to heat the rubber promotes the breaking of sulfur cross-links [13].…”
Section: Introductionmentioning
confidence: 99%
“…The microwave devulcanization, used in this study, has proved to be an efficient technique. This method enables to apply large amounts of energy rapidly and uniformly to the rubber, without using chemical reagents during the process [17,18], which makes it an eco-friendly process [19]. The energy used to heat the rubber promotes the breaking of sulfur cross-links [13].…”
Section: Introductionmentioning
confidence: 99%
“…The process has physical nature, i.e. it does not involve chemicals during the process and due to this reason is named ecofriendly 39 . Devulcanization of elastomers by microwaves shows promising results for recycling rubber 3,10,[12][13][14][15][16][17][18]40 .…”
Section: Introductionmentioning
confidence: 99%
“…This technique is widely mentioned by the literature to detect the status of devulcanization of elastomers 4,5,[14][15][16]24,31,32,39,41,[43][44][45][46][47][48][49][50][51][52] . In general, the content of soluble material (sol) increases with the increasing of devulcanization degree, due to the breaks of the cross-linkings and, consequently, the release of these molecules from the three-dimensional network of vulcanized rubber.…”
Section: Introductionmentioning
confidence: 99%
“…The authors highlighted the beneficial effects of DPDS on the efficiency of microwave devulcanization process. In another study, Hong et al [14] also compared devulcanization performance of microwave and ultrasonic procedures and concluded that microwave technique is better than ultrasonic method. To improve devulcanization efficiency and reduce treatment energy, promising new approach consists of impregnation of the waste rubber with solvent and then heat treating the impregnated material with microwave radiation.…”
Section: Introductionmentioning
confidence: 99%